2021
DOI: 10.3390/children8090742
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Movement Skills and Physical Activity of 3–4-Year-Old Children within Early Childhood Centers in New Zealand

Abstract: We sought to describe and explore relationships between fundamental movement skills (FMS) and level of physical activity (PA; light-, medium-, vigorous, and kCal/hour) in preschool children, aged 3–4-years-old, across four early childhood education (ECE) settings. Children’s FMS were assessed using the Test for Gross Motor Development-2 (TGMD-2; n = 81) and PA via accelerometers (S = 53). Eighty-four children participated, with 50 in both assessments. The TGMD-2 showed as the children got older, their locomoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(65 reference statements)
2
2
0
1
Order By: Relevance
“…This study showed that the development of locomotor ability, ball skill ability, and gross motor movement of left-behind children in each age group differed significantly with age and showed an overall increasing trend, which was consistent with the results of other prior studies [56]. It has been shown that children aged 3-6 are at a critical time in developing motor skills [57].…”
Section: Plos Onesupporting
confidence: 91%
“…This study showed that the development of locomotor ability, ball skill ability, and gross motor movement of left-behind children in each age group differed significantly with age and showed an overall increasing trend, which was consistent with the results of other prior studies [56]. It has been shown that children aged 3-6 are at a critical time in developing motor skills [57].…”
Section: Plos Onesupporting
confidence: 91%
“…In Hong Kong, Chow et al (2015a) indicated that kindergartens arrange less than 30 min for physical activities in a half-day session; children are primarily sedentary in the remaining class time. Similar findings have been reported in Western countries such as New Zealand (Ali et al, 2021), Australia (Ellis et al, 2017), and the US (Willis et al, 2021), where kindergarten children spend around 70% of their time sitting, standing, and engaging in other sedentary behaviors.…”
Section: Implementation Of Physical Activities In Kindergartens: Cont...supporting
confidence: 85%
“…As for the stress subscale consisted 2, 4, Health, sport, rehabilitation Health, sport, rehabilitation Здоров'я, спорт, реабілітація Здоров'я, спорт, реабілітація Здоровье, спорт, реабилитация Здоровье, спорт, реабилитация 2023 9(3) 54 7, 9, 15, 19, and 20 question items. Stress level was categorized as normal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26), severe (27 -34) and very severe (35)(36)(37)(38)(39)(40)(41)(42). Based on previous studies, this instrument has a Cronbach's coefficient of depression = 0.81, anxiety = 0.78 and stress = 0.88.…”
Section: Mental Healthmentioning
confidence: 99%
“…Several factors that cause the decrease on fundamental movement skills were lockdown and stay at home policies [37,38]. Improving the ability of fundamental movement skills has the potential to create an active lifestyle [39] and the basic capital for engaging in physical activity [40], physical education and sports. For example, when the fundamental movement skills is low, it will cause athletes difficult to learn and develop skills in sports [41,42].…”
Section: Introductionmentioning
confidence: 99%